Hazards of Pharmaceuticals in Water as New Area in Eco-Pharmacovigilance Research - Alshakka, Mohammed; Mohamed Izham Mohamed Ibrahim, Mohamed Izhamx; Azmi Hassali, Mohamed; Palaian, Subish; Aljadhey, Hisham (Journal of Pharmacy Practice and Community Medicine)
Pharmaceuticals in water can have potential toxic effects on environment and human. It is becoming an emerging research area. Pharmaceuticals have received a growing attention from environmental and health agencies all over the world due to recent studies showing the occurrence of pharmaceutical compounds in environment, especially in water bodies and have become one of the emerging water pollutants. The aim of this review article is to study the hazards of pharmaceuticals in water reported in the literature in order to promote the safe use of medicines among the general public. The aim of this article is to increase the environmental knowledge of pharmaceuticals and to draw attention of pharmacovigilance researcher for more awareness of some of the emerged problems caused by medicines. Detailed systematic review of the existing literature was carried out investigating the issue understudy. The review process included Pubmed database, Google Scholar, and other online resources available in the university library. The data obtained from the literature review were categorised before being analyzed by the researchers. Minor amount of medications in the water like in nanograms to low micrograms are already reported in per litre range including surface waters, wastewater, and groundwater and, to a lesser extent, drinking-water. Advances in analytical technology have been a key factor in the detection of the occurrence of these pharmaceuticals. Their presence in water, even at a very low concentration, has raised concerns among stakeholders, such as drinking water regulators, governments, water suppliers and the public regarding the potential risks to human health. The awareness about Ecopharmacovigilance as new science concern with the detection, assessment, understanding, and prevention of adverse effects or other problems related to the presence of pharmaceuticals in the environment, which affect human and other animal species and the environmental knowledge of pharmaceuticals must be increase. Ecopharmacovigilance issues must be urgently addressed.
Keywords: Ecopharmacovigilance; Pharmaceuticals; Pharmaceutical Analysis; Pharmacovigilance; Water